2008
DOI: 10.1002/path.2424
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide analysis of DNA copy number alterations and gene expression in gastric cancer

Abstract: Genomic copy number aberrations (CNAs) are believed to play a major role in the development and progression of human cancers. Although many CNAs have been reported in gastric cancer, their genome-wide transcriptional consequences are poorly understood. In this study, to reveal the impact of CNAs on genome-wide expression in gastric cancer, we analysed 30 cases of gastric cancers for their CNAs by array comparative genomic hybridization (array CGH) and 24 of these 30 cases for their expression profiles by oligo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
99
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(109 citation statements)
references
References 21 publications
10
99
0
Order By: Relevance
“…Of multiple locus of gene amplification and deletion, amplification of 2p24, 3q26, 5p13, 5p15, 6p21, 7q21, 8p23, 8q22, 8q24, 10q26, 11p11, 11p13, 11q13, 16p13, 17q12, 19q12-13, 20q13 and loss of 4q34, 9p21, 10q23, 19p13, 19q13 were consistent with the previous report in gastric cancer tissue or gastric cancer cell lines. [10][11][12][13][14][15][16][17][18][19][20][21] Most amplification loci were unique to single patients. The results thus suggest genetic alternations are less frequent in poorly differentiated gastric cancers and vary among individuals.…”
Section: Genomic Alternations In Poorly Differentiated Gastric Cancersmentioning
confidence: 99%
“…Of multiple locus of gene amplification and deletion, amplification of 2p24, 3q26, 5p13, 5p15, 6p21, 7q21, 8p23, 8q22, 8q24, 10q26, 11p11, 11p13, 11q13, 16p13, 17q12, 19q12-13, 20q13 and loss of 4q34, 9p21, 10q23, 19p13, 19q13 were consistent with the previous report in gastric cancer tissue or gastric cancer cell lines. [10][11][12][13][14][15][16][17][18][19][20][21] Most amplification loci were unique to single patients. The results thus suggest genetic alternations are less frequent in poorly differentiated gastric cancers and vary among individuals.…”
Section: Genomic Alternations In Poorly Differentiated Gastric Cancersmentioning
confidence: 99%
“…Tsukamoto et al observed higher frequencies of DNA copy number aberrations, especially in the case of 20q13 chromosome gain, which was detected in 97% of cases, compared to other studies (Tsukamoto et al, 2008). They used laser microdissection method to isolate tumour cells, therefore their samples contained fewer cells from tumour microenvironment.…”
Section: Chromosomal Instability (Cin) and Aneuploidymentioning
confidence: 96%
“…CIN is due to the imbalanced division of chromosomes to daughter cells upon mitosis and results in the loss or gain of DNA during cell division [14]. Copy number gains at 8q, 12q, 13q, 17q, and 20q and copy number losses at 3p, 4q, 5q, 15q, 16q, and 17q are frequently noted in GCs [15][16][17][18]. CIN is involved in focal gene amplifications as well as to chromosomal gains and losses.…”
Section: Cancer Therapy and Oncology International Journalmentioning
confidence: 99%